1998
DOI: 10.1016/s0014-5793(98)00572-9
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a native titin fragment to actin is regulated by PIP2

Abstract: Titin is a giant protein which extends from Z-line to M-line in striated muscles. We report here the purification of a 150-kDa titin fragment, obtained after V8 protease treatment of myofibrils. This polypeptide was located at the N1-line level, in a titin part known to exhibit stiff properties correlated to an association with actin. By solid or liquid phase binding assays and cosedimentation, we have clearly demonstrated a direct, saturable and relative high affinity binding of the native titin fragment to F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 39 publications
0
21
0
1
Order By: Relevance
“…Consistent with this, Astier et al (13) calculated an apparent binding affinity ( K D ) in the low micromolar range for the binding of actin to titin's PEVK region, and Kulke et al (188) and Yamasaki et al (418) proposed that this binding might be modulated by dynamic extrinsic factors, such as local ionic strength and temperature. Using in vitro motility assays and cosedimentation studies, they demonstrated that increases in ionic strength or temperature augmented binding significantly, which suggested the involvement of hydrophobic interactions in the association of actin with the PEVK region of titin (188, 418).…”
Section: Titinmentioning
confidence: 85%
“…Consistent with this, Astier et al (13) calculated an apparent binding affinity ( K D ) in the low micromolar range for the binding of actin to titin's PEVK region, and Kulke et al (188) and Yamasaki et al (418) proposed that this binding might be modulated by dynamic extrinsic factors, such as local ionic strength and temperature. Using in vitro motility assays and cosedimentation studies, they demonstrated that increases in ionic strength or temperature augmented binding significantly, which suggested the involvement of hydrophobic interactions in the association of actin with the PEVK region of titin (188, 418).…”
Section: Titinmentioning
confidence: 85%
“…Recently, a correlation between titin size and TFL was reported based on comparisons of multiple rabbit skeletal muscles [5], and it was suggested therefore that titin may play a role in TFL regulation. Titin could affect TFL directly (titin is known to interact with actin [4649]) or indirectly, for example by altering the slack sarcomere length. We tested the proposal that titin affects TFL in the heart by using the Rbm20 ΔRRM mouse model in which altered splicing results in titin molecules that are much larger than in wild type mice [35].…”
Section: Discussionmentioning
confidence: 99%
“…The I-band region of titin probably is understood best and consists of the proximal immunoglobulin (Ig) tandem domain segment closest to the Z-disc, the N2A domain, the PEVK segment (rich in proline [P], glutamate [E], valine [V], and lysine [K]), and the distal Ig segment (closest to the A-band) (Fig. Titin also is known to interact with actin in a variety of ways (3,11,29,35,41,44,47), and if the extent of such interactions would change with muscle activation or force production, as has been suggested (54), it would change titin's free spring length and thus its stiffness. The so-called N2B segment is another spring element that is exclusive to cardiac titin.…”
Section: Titin's Stiffness Regulation Titin Structure and Functionmentioning
confidence: 99%